The Saddle: Our Eastern Cultural Heritage - Gráfik, Imre (Ethnographica et Folkloristica Carpathica, 2021)
The study summarizes the most important knowledge about the saddle, the eastern heritage of Hungarian culture, based on the results of the research and an exhibition. Animal husbandry, especially keeping horses, has always played a very important part in Hungarians life. Saddling horses was significant up until the middle of the 20th century in Hungary, we have information about it from noblemen, the aristocracy, the upper social stratas, as well as from peasants and market town inhabitants. Objects and memories connected to riding culture, riding as a way of life, were present in the memory of the upper social classes and in folklore. There were different types, varieties of saddles, just as there were varieties of almost all the objects in our culture, depending on who used them and for what purposes. In general we can say that as the terms and conditions of life changed so objects were transformed and developed. The same is true for saddles, they belong to a group of objects which gained their final, almost perfect shape very early in time, so very few changes were made to them. The saddles used by Hungarians were very suited to riding. The big advantage of wooden saddles is that they spare horses. There are two basic types of saddles usually known as the western and eastern types. From a professional point of view, on the basis of examined material, we speak of the pommel-sole/panel type and the fork-side panel/bar type. The Hungarian saddle belongs to the Eastern type. A unique and famous variety of the Hungarian saddle is the Tiszafüred saddle. Light cavalry equipped with Hungarian harness spread around Europe, so Hungarian type saddles (Hussar saddle ) were an essential part of military equipment. Nowadays there is an increased interest in the riding tradition, and the historical past, and attention is focused on the Hungarian wooden saddle that has been used successfully over the centuries.